Social Science Education Learning Model Based on Baduy Luar Local Culture for Elementary Students - Ajat Sudrajat; Cecep Kustandi; Ojat Darojat (Journal of Science and Education (JSE), 2026)
Social studies education is a subject designed to equip students with knowledge, social skills, and positive attitudes. Therefore, an in-depth learning approach can serve as an alternative to enhance pedagogical practices for elementary school students. The enhancement of pedagogical practices must also be supported by the implementation of appropriate learning models for elementary school students. This study aims to analyze the role of a social studies learning model based on the local culture of the Baduy Luar community. A qualitative approach with a case study design was used to explore the culture-based learning model. Data collection was conducted through in-depth interviews with five elementary school teachers and five fifth-grade elementary school students in Lebak Regency, Banten Province. Additionally, participatory observation and documentation were carried out. The results of this study indicate that a local culture-based learning model can support a meaningful and in-depth learning process. This is evident in the students’ ability to understand the way of life of the Baduy Luar community, such as preserving and respecting the environment. This learning model also encourages teachers and students to create a mindful learning environment where students can understand learning objectives and are intrinsically motivated to learn. This study has implications suggesting that a learning model based on local culture can support students’ ability to construct their own knowledge and apply it in real life. Thus, the cultural values of the Baduy Luar community can serve as a foundation for students to identify and analyze situations in their surrounding environment. Additionally, students can deepen their sense of love for their region